Penarikan Uang Kembalian Sebagai Donasi Prespektif Hukum Ekonomi Syariah - Arriza Qotrunnada; Makrum Kholil; Nadila Emiliyani (Fakultas Syariah Universitas Islam Negeri (UIN) K.H. Abdurrahman Wahid Pekalongan, 2022)
This article examines the withdrawal of change as a donation to the Retail Franchise at Alfamart Kebonsari Petarukan Pemalang. His writing was inspired by the fact that Alfamart's management had difficulty in providing second change, so the policy was to choose change into donations. The problem is how to practice withdrawing money as a donation, how and how to practice withdrawing money from the perspective of Sharia Economic Law. This research uses an approach approach other than that the data sources used are primary and secondary data sources, primary data sources are direct data sources obtained by interview and observation techniques while the primary data sources in this study are sellers, buyers, cashiers. While secondary data sources are obtained from other sources such as books, journal articles, and other information that will be discussed by researchers as supporters. With an approach approach, the results of the study show that: the practice of withdrawing change as a donation at the Retail Franchise at Alfamart Kebonsari Petarukan Pemalang is carried out voluntarily, without coercion from consumers; and the amount generated is very large, because it is distributed to the poor, so withdrawal of change as a contribution in Economic Law is allowed because it is suitable for worship.